Workers' Compensation “Reforms,” Choice of Medical Care Provider, and Reported Workplace Injuries - Boden, Leslie I.; Ruser, John W. (The Review of Economics and Statistics, 2003)
In the 1990s, many states passed workers' compensation laws to control cost growth. Using a difference-in-differences approach, we determine the impact of these laws on the frequency of reported workplace injuries. In response to restrictions that make it more difficult to file claims, reported days-away-from-work injuries decline, accounting for between 7.0% and 9.4% of the dramatic fall in their frequency in 1991–1997. At the same time, these filing disincentives appear to account for 6.8% of the increase in cases with only restricted work activity, although the evidence is weaker for these injuries. Restricting workers' choice of medical care provider did not appear to reduce the frequency of cases in any nonfatal injury category.